Financial Crises and Malaysia Trade Impact and Forecasting - Diana Nabila Chau, Abdullah (2011)
Financial crises are an ongoing challenge in the modern world with much complicated global economics. Malaysia itself has gone through severe crises in about once in a decade started in late 20th century. Many economy sectors had been affected by the crises, but the highlight in this study is focused on the impacts of financial crises on the trade of Malaysia. The objective is to forecast the trend of Malaysia trade when influenced by the shocks in the economy. This study applies Granger causality test and ARIMA model into the data of Malaysian trade from 1947 to 2009. It is very crucial to analyze and forecast these impacts since Malaysia is one developing country with a growing-open market economy and mostly dependent to the exports. The importance of export in boosting Malaysia economy was supported by the findings of this study in which it shows export does Granger cause total trades for before and after the crises. Due to the impacts of financial crises on Malaysia trade, Malaysia could focus on domestic demand, build the country’s comparative advantage in manufactured exports, or expand the export prospects. Nevertheless, the policy implication highlighted the importance to stimulate exports considering it is the major growth-key for Malaysia economy.